Convergence of an iteration leading to a solution of a random operator equation. (1999) - Choudhury, Binayak S.; Ray, M.
Abstract : In the present paper, we define a random iteration scheme and consider its convergence to a solution of a random operator equation. There is also a related fixed point result.